2020
DOI: 10.1186/s12889-020-09025-5
|View full text |Cite
|
Sign up to set email alerts
|

Regret over the delay in childbearing decision negatively associates with life satisfaction among Japanese women and men seeking fertility treatment: a cross-sectional study

Abstract: Background: Currently, in developed countries, increasing numbers of women and men are delaying childbearing but begin seeking fertility treatment later in life. Some women undergoing infertility treatment develop negative feelings such as depression associated with low life satisfaction and regret over the delay in childbearing. We therefore examine the association of life satisfaction with regret over the delay in childbearing decision and infertility-related factors among Japanese women and men seeking fert… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
12
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 42 publications
2
12
0
Order By: Relevance
“…The study conducted by Adachi et al among 449 Japanese patients seeking fertility treatment showed that the mean score of SWLS for women was significantly lower than that for men (women = 21.2 vs. men = 22.4) [ 49 ]. In another study conducted on infertile women in Iran, results indicated that women undergoing infertility treatments were quite satisfied with their lives (score 21–25) (which corresponds to a value of 6–7 on a sten scale) [ 50 ].…”
Section: Discussionmentioning
confidence: 99%
“…The study conducted by Adachi et al among 449 Japanese patients seeking fertility treatment showed that the mean score of SWLS for women was significantly lower than that for men (women = 21.2 vs. men = 22.4) [ 49 ]. In another study conducted on infertile women in Iran, results indicated that women undergoing infertility treatments were quite satisfied with their lives (score 21–25) (which corresponds to a value of 6–7 on a sten scale) [ 50 ].…”
Section: Discussionmentioning
confidence: 99%
“…A Japanese study examined the association of life satisfaction with regret over delaying childbearing decisions and infertility-related factors among Japanese women and men seeking fertility treatment. Infertile Japanese women regretted delaying fertility decisions, and this was negatively correlated with life satisfaction (Adachi et al, 2020). G.…”
Section: Discussionmentioning
confidence: 99%
“…A Japanese study examined the association of life satisfaction with regret over delaying childbearing decisions and infertility-related factors among Japanese women and men seeking fertility treatment. Infertile Japanese women regretted delaying fertility decisions, and this was negatively correlated with life satisfaction (Adachi et al, 2020). G. L. Lee and colleagues (2012) identified four aspects of the symbolic meaning of childbearing of concern to Hong Kong Chinese women receiving IVF treatment: focusing on the sense of self, cultural values, existential purpose, and relationship with others.…”
Section: Discussionmentioning
confidence: 99%
“…Most previous studies on well-being related to pregnancy focused on infertility; there is consensus that infertility lowers the level of well-being, particularly for women [4][5][6][7] and successful pregnancy leads to an improvement in well-being [8,9]. Some studies focused on people with infertility treatment and revealed that women regret their decision to delay childbearing while they were younger and that it leads to a low level of well-being [10,11]. Cooke et al [10] claim that a complex interplay of factors outside of women's control and/or conscious choice determines childbearing delay.…”
Section: Introductionmentioning
confidence: 99%
“…Cooke et al [10] claim that a complex interplay of factors outside of women's control and/or conscious choice determines childbearing delay. Furthermore, according to Bunting et al [12], a lack of fertility knowledge, including age-related infertility and risk factors of infertility, contributes to the childbearing delay decision, leading to regret at an older age, to which Japanese women are not an exception [11].…”
Section: Introductionmentioning
confidence: 99%